Immunophenotypic analysis of cell cycle status in acute myeloid leukaemia: relationship to cytogenetics, genotype and clinical outcome. (20th April 2018) - Sellar, Rob S.; Gale, Rosemary E.; Khwaja, Asim; Garbowski, Maciej; Loddo, Marco; Stoeber, Kai; Williams, Gareth H.; Linch, David C.
Summary: Cell cycle status may play an important role in directing patient therapy. We therefore determined the cell cycle status of leukaemic cells by immunophenotypic analysis of bone marrow trephine biopsies from 181 patients with acute myeloid leukaemia (AML) and correlated the results with biological features and clinical outcome. There was considerable heterogeneity between patients. The presenting white cell count significantly correlated with the proportion of non‐quiescent cells ( P  <   0·0001), of cycling cells beyond G1 ( P  <   0·0001) and the speed of cycling ( P  <   0·0001). Profiles in acute promyelocytic leukaemia (APL) differed from non‐APL and were consistent with more differentiated cells with reduced proliferative potential, but no significant differences were observed between non‐APL cytogenetic risk groups. NPM1 mutations but not FLT3 internal tandem duplication ( FLT3 ITD ) were significantly associated with a higher proportion of cells beyond G1 ( P  =   0·002) and faster speed of cycling ( P  =   0·003). Resistance to standard cytosine arabinoside and daunorubicin induction chemotherapy was significantly related to a slower speed of cycling ( P  =   0·0002), as was a higher relapse rate ( P  =   0·05), but not with the proportion of non‐quiescent cells or actively cycling cells. These results show a link between the cycling speed of AML cells and the response to chemotherapy, and help to identify a group with a very poor prognosis.